A study of critical success factors on software quality assurance of cloud networking devices - Shin-Jer Yang; Chung-Hsi Liao (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
In recent years, many more enterprises and organizations are embracing cloud computing for its commercial benefits and competitive advantages. However, these companies have prioritized hardware specifications when evaluating cloud networking devices, often neglecting the importance of software quality as a result. Most cloud networking devices currently offered on the market include embedded software systems, which mean that software and hardware compatibility can be one of the most essential characteristics to look for. In order to investigate the critical success factors (CSFs) for the software quality assurance (QA) of cloud networking devices, this study employed a Plan-Do-Check-Act (PDCA) research framework. Important Software QA factors from relevant IEEE standards and hardware factors related to software quality were then employed in the 4 facets of the PDCA process to conduct a 2-stage analysis. For the first stage of this study, 5 experts were interviewed and asked to complete a survey form and select CSFs that were then used to generate a questionnaire for the second stage where a total of 15 experts and QA engineers were invited to fill out questionnaires. Completed questionnaires were then subject to an analytic hierarchy process (AHP) to calculate the weight and priority orders for each of the CSFs. The overall results of Stage 2 indicate that Cloud devices security testing, Security of cloud networking devices, and Resources and their allocation are the top three orders of all CSFs when experts take a real concern in software QA of cloud networking devices.